Female Entrepreneurs as Brand Ambassadors and Rural Tourism Development during a Crisis - Stylianou, Christiana; Liasidou, Sotiroula; Aslanidou, Anastasia (My University, 2022)
Admittedly, tourism is one of the most significant economic engines for achieving growth and financial sufficiency in island states (Lin, Yang and Li, 2019). Being a tourism-dependent island, Cyprus’s economy is mainly driven by tourism activities (Sharpley, 2001). Female entrepreneurship plays an essential role in an industry’s growth. Researching female entrepreneurship within rural contexts can shed light on the societal and institutional influences that rural areas exert on female entrepreneurs (Wu, Li and Zhang, 2019). Stakeholders in rural areas in Cyprus, such as ‘Orini Larnakas’ (Rural Larnaka), focus on creating tourism-related enterprises through female entrepreneurs. Relevant research examines rural business development; however, its association with tourism and place branding deserves attention, especially during periods of crisis (Li et al., 2021; Coles, Ritchie and Wang, 2021). The Covid-19 pandemic posed a threat to the recovery of tourism, especially in the vulnerable rural areas, and entrepreneurs’ role is central to their enterprises’ recovery and their destination’s reputation. Residents’ communication about their region as a tourist attraction has started recognized in place branding (Wassler, Wang and Hung, 2021; Jeuring and Haartsen, 2017). Entrepreneurs as brand ambassadors of a region is a relatively new phenomenon in regional marketing and rural development, but it is steadily becoming more entrenched as a practice. Such novel elements of regional marketing might be a reaction to rural tourism development during a crisis (Stephens, Cunningham, and Kabir, 2021; Eichelberger et al., 2020). Research has shown that female entrepreneurs are involved in regional marketing and place branding practices and tend to form ambassador networks (Poulaki, Lagou and Valeri, 2021; Jeuring and Haartsen, 2017; Andersson and Ekman, 2009). The purpose of this study is twofold: first, to examine how a group of rural area-based female business owners become place ambassadors, and second, how female entrepreneurs enact place branding to achieve rural tourism development during a crisis, notably the Covid-19 pandemic. Empirical evidence will be derived from qualitative research through twenty-five 25) semi-structured face-to-face interviews with female micro-entrepreneurs in the ‘Orini Larnaka’s’ area in Cyprus. The selected sample method is purposive and thematic analysis will be employed. While a pandemic exposes breaches and chronic deficits of established destination management practices, the expected findings will indicate how female entrepreneurs can overcome the obstacles that a crisis brings and the association between female entrepreneurship practices and place branding, aiming to create spaces of coexistence to accomplish tourism development in rural areas. Our study will contribute to the literature on female entrepreneurship in several ways. Initially, it will provide insights into unique practices and interactions underpinned by the joint endeavors of a group of entrepreneurs aiming to engage in place branding. Secondly, it will give a context-based theorization and shed light on how a context (rural region) influences and is influenced by female entrepreneurship. Lastly, it will connect entrepreneurship with a significant exogenous shock, explaining how a crisis, such as a pandemic affects the place branding of a destination.
Keywords: Female Entrepreneurship; Tourism; Covid 19; Brand Ambassador; Cyprus